Peranan Perempuan Kelompok Sentosa Sasak Tenun di Desa Wisata Pringgasela Kabupaten Lombok Timur - Rohmi, Ziyadatur; Mahagangga, I Gusti Agung Oka (JURNAL DESTINASI PARIWISATA, 2020)
The gedogan woven fabric business is one of the businesses that can contribute to improving the community's economy as well as being supporting tourism product activities in East Lombok Regency. Women have the power to be more empowered in improving family welfare. This study aims to determine the role of women in the development of the gedogan weaving business in the Sentosa Sasak Tenun Group at Pringgasela Tourism Village, East Lombok Regency. In this study using qualitative and quantitative data types, while the data sources used are primary and secondary. Data collection techniques in this study using observation techniques, in-depth interviews and documentation. The informant determination technique used is purposive sampling technique. The data analysis technique used is qualitative descriptive data analysis. The results showed that the role of women in the Sentosa Sasak Tenun Group on productive roles was as weaving craftsmen, farmers, farm laborers, farm laborers, breeders, and home traders. The reproductive role of women weavers is managing the household. Meanwhile, the social role in the community, namely, as a member of the Muslimat related to religious events, cooperation activities between communities or traditional events which in Sasak is called gawe belek, and the health group namely Work Health Efforts. Of the three role models, the main role of women in the Sentosa Sasak Tenun Group is their reproductive role, because as a wife and mother, the nature of a woman is managing household affairs. Keywords: women's role, small business, crafts, weaving, tourism village